1973
DOI: 10.1002/cber.19731060822
|View full text |Cite
|
Sign up to set email alerts
|

Reaktionen von Metallcarbonylen mit Aziridin

Abstract: Die Hexacarbonyle von Chrom, Molybdan und Wolfram setzen sich photochemisch oder thermisch mit Aziridin (in) zu Komplexcn M(CO)fj-,in, (n = I, 2, 3) um. Aus den cis-Bis(aziridin)tctracarbonylmetall-Verbindungen entstehen in Gegcnwart von protischen Losungsmittelii durch Reaktion zwischen zwei Aziridinliganden Tetracarbonylkomplexe M(C0)ddiin mit dem N-(2-Aminoathyl)aziridin-Chelatligandcn (dun). Aus Tc-CH3C-HdMn(C0)3 und in bzw. diin werdeii die Verbindungen x-CH3C:~H~Mn(CO)~in bzw. (x-CH3CsH4)-(CO)2Mn~-diin-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…However, this reaction has been described in only a few papers and concerns specific reactions, namely, the synthesis of complexes of aziridines with transition metals. Transition metal (Cr, Mo, W, Cd, Co)-mediated ring-opening reactions of aziridine ligands yielding aminoethylaziridine-N,N′ complexes by 'aziridine dimerization' were first observed by Beck 24 and Fritz 25 and then by others. 26,27 Recently, synthesis, X-ray structural characterization, antimicrobial and cytotoxic effects of aziridine and 1-(2-aminoethyl)aziridine complexes of Cu(II) and Pd(II) have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…However, this reaction has been described in only a few papers and concerns specific reactions, namely, the synthesis of complexes of aziridines with transition metals. Transition metal (Cr, Mo, W, Cd, Co)-mediated ring-opening reactions of aziridine ligands yielding aminoethylaziridine-N,N′ complexes by 'aziridine dimerization' were first observed by Beck 24 and Fritz 25 and then by others. 26,27 Recently, synthesis, X-ray structural characterization, antimicrobial and cytotoxic effects of aziridine and 1-(2-aminoethyl)aziridine complexes of Cu(II) and Pd(II) have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…The 49 but without any structural characterization. Beck et al also observed the first "aziridine dimerization" induced by metal coordination.…”
Section: Resultsmentioning
confidence: 99%
“…with hydrido carbonyl complexes to form β-aminoacyl complexes via M-C addition [42][43][44][45][46] or with halogenido carbonyl complexes to form five-membered aminooxycarbene complexes. 47,48 Transition metal-mediated ring opening reactions of aziridine ligands yielding aminoethylaziridine-N,N′ complexes by "aziridine dimerization" was first observed by Beck et al 49 and Fritz et al 50 The first examples of such an aziridine dimer template have been structurally characterized by X-ray determination in the case of a cationic Co(III) complex bearing two dimerized 2-methylaziridine ligands. 51 We later reported further examples of analogous complexes with dimerized aziridine ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beck et cd. haben schon früher die R eaktivität von A ziridinen ge genüber M etallcarbonylen untersucht [5]. Sie ha ben vor allem RingÖffnungsreaktionen beobachtet.…”
Section: Introductionunclassified